BIOMONITORING PENCEMARAN LINGKUNGAN MENGGUNAKAN KUNANG KUNANG (Lampyridae) - Hendriawan; Sovinatun Najah; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Environmental pollution is a major issue that affects ecosystem balance and biodiversity. Biomonitoring using bioindicator organisms is an effective approach to assess environmental quality. Fireflies (Lampyridae) are insects that are highly sensitive to environmental changes, including water pollution, chemical exposure, and light pollution. This study aims to analyze the role of fireflies as bioindicators of environmental pollution with a case study in Sembung Village, Narmada District, West Lombok Regency. The method used in this study is a literature review combined with field observation. The results show that fireflies in Sembung Village are increasingly rarely found, indicating a decline in environmental quality. This condition is suspected to be influenced by water pollution, pesticide use, habitat changes, and light pollution. Therefore, fireflies can be used as effective bioindicators in monitoring environmental quality, especially in rural ecosystems.